2006
DOI: 10.1002/pola.21265
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical analysis of metallocene‐catalyzed ethene–α‐olefin copolymers: The influence of the length and number of the crystallizing side chains

Abstract: Copolymers of ethene and 1-octene, 1-dodecene, 1-octadecene, and 1-hexacosene were carried out with [Ph 2 C(2,7-ditert BuFlu)(Cp)]ZrCl 2 /methylalumoxane as a catalyst to obtain short-chain branched polyethylenes with branch lengths of 6-26 carbon atoms. This catalyst provided high activity and a very good comonomer and hydrogen response. In this study, the influence of the length and number of the side chains on the mechanical properties of the materials was investigated. The crystalline methylene sequence le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 43 publications
6
67
0
3
Order By: Relevance
“…It might be either an intralamellar or a lamella boundary crystallization. Piel et al [8] reported that this crystallization accounts for an additional mechanical transition around +45 °C, which roughly coincides with the additional melting peak in DSC, i.e. this transition is the side-chain crystallite melting temperature.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…It might be either an intralamellar or a lamella boundary crystallization. Piel et al [8] reported that this crystallization accounts for an additional mechanical transition around +45 °C, which roughly coincides with the additional melting peak in DSC, i.e. this transition is the side-chain crystallite melting temperature.…”
Section: Discussionmentioning
confidence: 85%
“…One part of the question what happens to those longer side chains was already answered by Piel et al [8] by finding a weak crystallization of the tetracosene branches (C24) from the hexacosene comonomer. The question remains, however, where this crystallization is taking place.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations